Perbaikan Modul Training Primary Processing di PT. X - Ngono, Elvira Lionora; Palit, Herry Christian (Jurnal Titra, 2014)
PT. X provides training programs to improve performance of its employees, that implemented by the Technical Training Department. One of the things that support the training program is the training module. Primary Processing training modules are not appropriate anymore with the current situation, therefore the improvements are needed. Training module at Primary Processing, a total of 13 modules are improved based on Best Training Practice (BTP) method. The results of these training module improvements are expected to help the implementation of the training program, so it can be effective and efficient training.